Educating Children Without Violence in the Perspective of Hadith: A Thematic Hadith Study and its Relevance to Parenting Concepts - Nurdin Rizki; Hairullah Hairullah; Hidayati Hidayati (STAI Serdang Lubuk Pakam, 2026)
The increasing prevalence of violence in childrearing has intensified the need for more humane and child-centered parenting approaches. While contemporary parenting theories advocate non-violent education, misconceptions surrounding certain prophetic traditions are still frequently used to justify harsh disciplinary practices in Muslim families. This study aims to examine the concept of non-violent parenting in the Hadith through a thematic (hadith maudhū‘ī) approach and to analyze its relevance to contemporary parenting theories. Employing a qualitative library research design, data were collected from authentic hadiths related to child education and analyzed through thematic classification, contextual interpretation, and comparison with positive parenting and emotional regulation frameworks. The findings reveal that Prophetic parenting emphasizes compassion (raḥmah), gentleness (al-rifq), role modeling, dialogical communication, gradual habituation, and proportionate discipline rather than physical punishment. The study proposes the concept of Humanistic Prophetic Parenting, integrating thematic hadith analysis with modern parenting principles. This model provides a theological and psychological foundation for promoting child-friendly parenting and preventing violence against children in contemporary Muslim families.